2008
DOI: 10.1136/bjo.2008.140509
|View full text |Cite
|
Sign up to set email alerts
|

23-gauge versus 20-gauge system for pars plana vitrectomy: a prospective randomised clinical trial

Abstract: The 23-gauge system for pars plana vitrectomy offers significantly higher patient comfort during the early postoperative period. Time of surgery is almost equal--a shorter time for wound closure is neutralised by a longer vitrectomy time in the 23-gauge group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 9 publications
4
70
0
2
Order By: Relevance
“…Postoperative BCVA and IOP were measured at 1 day, 1 week, and 1 and 3 months after surgery. As a substitute for a patient survey on the postoperative discomfort, the degrees of postoperative conjunctival and corneal change were qualitatively graded using an earlier reported standardized scale 19,20 with some modifications. Briefly, each category of conjunctival injection, conjunctival oedema, subconjunctival haemorrhage, and corneal oedema were scored by slit-lamp examination as 0 (absent), 0.5 (trace), 1 (mild), 2 (moderate), and 3 (severe).…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative BCVA and IOP were measured at 1 day, 1 week, and 1 and 3 months after surgery. As a substitute for a patient survey on the postoperative discomfort, the degrees of postoperative conjunctival and corneal change were qualitatively graded using an earlier reported standardized scale 19,20 with some modifications. Briefly, each category of conjunctival injection, conjunctival oedema, subconjunctival haemorrhage, and corneal oedema were scored by slit-lamp examination as 0 (absent), 0.5 (trace), 1 (mild), 2 (moderate), and 3 (severe).…”
Section: Methodsmentioning
confidence: 99%
“…This difference was not statistically significant (P=.22). Smaller studies [8][9][10]12 demonstrated a statistically nonsignificant trend for fewer intraoperative retinal tears, and others 16,18,20,21 reported no intraoperative breaks in either group. To the best of our knowledge, our study is the first that has found a statistically significant reduction in the rate of intraoperative retinal break formation using transconjunctival cannulated PPV.…”
Section: Commentmentioning
confidence: 99%
“…Whereas some authors describe a shorter operation time for 23-7,11,12 and 25-gauge ppv, 5,7,12 respectively, others find no difference. 13,14 When comparing operation times, the exact procedure and its respective time requirement must be considered; for instance, a longer duration of the actual vitreous extraction that outweighs the benefit of the non-suture may be a result of a lower cutting rate. Moreover, the additional cataract operation performed in the present series must be accounted for about 10-15 min, putting the operation time in the present series more or less in the same order of magnitude as in most other trials.…”
Section: Discussionmentioning
confidence: 99%